2010
DOI: 10.1016/j.socscimed.2009.11.025
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of primary care to health and health systems in low- and middle-income countries: A critical review of major primary care initiatives

Abstract: a b s t r a c tIt has been 30 years since the Declaration of Alma Ata. During that time, primary care has been the central strategy for expanding health services in many low-and middle-income countries. The recent global calls to redouble support for primary care highlighted it as a pathway to reaching the health Millennium Development Goals. In this systematic review we described and assessed the contributions of major primary care initiatives implemented in low-and middle-income countries in the past 30 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
191
0
8

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 248 publications
(206 citation statements)
references
References 52 publications
4
191
0
8
Order By: Relevance
“…Agnes Binagwaho, MD Pediatr, (6) Flavia Bustreo, MD, (7,8) David Evans, PhD, (7,8) Richard GA Feachem, DSc Med, (9,10) Julio Frenk, MD, (11) Gargee Ghosh, MSc, (12) Sue J Goldie, MD, (11) Yan Guo, MPH, (13) Sanjeev Gupta, PhD, (14) Richard Horton, MedSci, (15) Margaret E Kruk, MD, (16) Adel Mahmoud, MD, (17) Linah K Mohohlo, MSc, (18) Mthuli Ncube, PhD, (19) Ariel Pablos-Mendez, MD, (20,21) K Srinath Reddy, DM Card, (22) Helen Saxenian, PhD, (23) Agnes Soucat, MD, (24) Karen H Ulltveit-Moe, PhD, (25) Gavin Yamey, MD.…”
Section: Salud Global 2035: Un Mundo Convergiendo En El Lapso De Una mentioning
confidence: 99%
See 1 more Smart Citation
“…Agnes Binagwaho, MD Pediatr, (6) Flavia Bustreo, MD, (7,8) David Evans, PhD, (7,8) Richard GA Feachem, DSc Med, (9,10) Julio Frenk, MD, (11) Gargee Ghosh, MSc, (12) Sue J Goldie, MD, (11) Yan Guo, MPH, (13) Sanjeev Gupta, PhD, (14) Richard Horton, MedSci, (15) Margaret E Kruk, MD, (16) Adel Mahmoud, MD, (17) Linah K Mohohlo, MSc, (18) Mthuli Ncube, PhD, (19) Ariel Pablos-Mendez, MD, (20,21) K Srinath Reddy, DM Card, (22) Helen Saxenian, PhD, (23) Agnes Soucat, MD, (24) Karen H Ulltveit-Moe, PhD, (25) Gavin Yamey, MD.…”
Section: Salud Global 2035: Un Mundo Convergiendo En El Lapso De Una mentioning
confidence: 99%
“…En varios países, las clínicas robustas de atención primaria con proveedores calificados y una infraestructura fuerte y cadenas de suministro de productos básicos han demostrado ser una plataforma eficaz para el FSS. 23 En algunos países, se han desarrollado sistemas de atención a pacientes crónicos en gran escala a fin de proporcionar servicios a los pacientes infectados con VIH; estos sistemas pueden ser utilizados para impulsar programas "de arranque" para las ENT crónicas. 24 Sin embargo, las clínicas de atención primaria y los trabajadores comunitarios de la salud por sí solos son insuficientes.…”
Section: Fortalecimiento De Los Sistemas De Salud Por Medio De Un Enfunclassified
“…16 The network has relied primarily on community health workers (behvarz) as first-line service providers. The behvarz are selected from the locality where they live, receive training for two years and provide basic services at a "health house".…”
Section: Health-care Financing and Delivery In Rural Parts Of The Islmentioning
confidence: 99%
“…38,40 Additionally, geographical access to facilities can be an important determinant of use. 45 One review 46 of largescale, compre hensive primary health-care initiatives showed that establish ment of a network of primary-care facilities can have an important eff ect on increasing coverage in underserved rural populations in particular.…”
Section: Human Resource Availability and Geographical Accessmentioning
confidence: 99%
“…46,78 Unless the bottlenecks faced by poor and marginalised people in access to and use of health interventions and services are explicitly addressed, inequities will probably worsen as more expensive and elaborate interventions are introduced. 79 We believe that our overview provides a broad summary of relevant information for health planners and policy makers that seek to reduce inequities and accelerate progress towards the health Millennium Development Goals and other commitments to children.…”
Section: Equity-focused Approachesmentioning
confidence: 99%